The Effect of Energy Gel Administration in Preventing Declining Running Performance of Healthy Recreational Runners - Salsabila Permata Sari; Patricia Roulina Purba; Carissa Ramadhania Oktaviani; Rendy Dijaya Muliadi; Lina Antono; Felicia Kartawidjajaputra (Sport and Nutrition Journal, 2025)
A half-marathon is a type of endurance sport that is increasingly popular in Indonesia. During endurance activities, the body experiences a decrease in glycogen reserves and blood glucose levels, which can lead to reduced physical performance and increased fatigue. Energy gels are concentrated sources of carbohydrates to provide fast-absorbing energy during exercise. Consuming energy gels during running is considered beneficial for maintaining performance and preventing fatigue. Most research on energy gel consumption focused on trained athletes; the effect of energy gel consumption for recreational runners, however, is unclear. The objective of this study was to examine the impact of energy gel consumption on maintaining running performance in healthy, recreational Indonesian half-marathon runners. In this crossover study, sixteen recreational runners received energy gel (28 g/serving carbohydrate), konjac jelly (4 g/serving carbohydrate), and mineral water supplementation on three separate occasions during their running. Self-reported performance data (running duration, distance, elevation, rate of perceived exertion, and heart rate) were collected using a web-based questionnaire after each session, and assessed with the Friedman Test and the Wilcoxon Signed Ranks Test. In this study, energy gel consumption significantly reduced the rate of perceived exertion (RPE) compared to mineral water consumption (p < 0.05). However, no significant effect on running duration (p>0.05) nor heart rate (p>0.05) was observed.